What's happened to paraphrenia? A case-report and review of the literature - Pelizza, L.; Federica, Bonazzi (Acta Biomedica Atenei Parmensis, 2010)
Paraphrenia is a chronic psychotic disorder similar to paranoid schizophrenia, but with a better-preserved affect and relation and a much less personality deterioration. It was firstly systematically described by Kraepelin in 1913 in order to define a group of psychotic patients who exhibited characteristic symptoms of dementia praecox, but with minimal disturbances of emotion and volition, and marked delusions. After the publication of the Mayer-Gross’s report in 1921, the view to differentiate paraphrenia from schizophrenia was considered to be unfounded and the term “paraphrenia” was not included in the current DSM-IV-TR diagnostic criteria. Consequently, now this disorder is infrequently diagnosed. However, several authors suggest that the concept of paraphrenia has not lost its usefulness. It seems to be that some psychiatrists recognize the illness, but labelled it as “atypical psychosis”, “schizoaffective disorder”, “delusional disorder” or “psychotic disorder not otherwise specified” for the lack of a better diagnostic category. Very few systematic studies on paraphrenia have been carried out in the past 70 years. Aim of this article is to describe a case of chronic delusional psychosis who meets the Ravindran’s modern diagnostic criteria for “paraphrenia redefined”, suggesting that it is possible to define and recognize the illness if the practitioners are induced to use a viable diagnostic entity. Further research would benefit paraphrenic and schizophrenic patients.